1979
DOI: 10.1093/ajcn/32.9.1769
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional deprivation in childhood and the body size, activity, and physical work capacity of young boys

Abstract: Clinical nutritional status and physical work capacity at submaximal level were assessed in 96 rural Hyderbad boys, 14 to 17 years of age. Data available on the previous nutritional status of these children when they were 5 years of age were used for classifying them into different nutritional grades. Factors responsible for undernutrition childhood continued to operate on later growth. Both height and weight at 5 years correlated well (P less than 0.001) with current height and weight. About 64% (P less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 13 publications
1
24
0
1
Order By: Relevance
“…Despite this socioeconomic effect, the present study does not show a consistent relation between nutritional status and levels of physical activity. This inconsistency was also observed in several other studies comparing nutritional groups within school-age populations (5,20,22,30,34). Peer pressure and survival needs are cited as the main reasons for this finding (22).…”
Section: Tablementioning
confidence: 56%
See 1 more Smart Citation
“…Despite this socioeconomic effect, the present study does not show a consistent relation between nutritional status and levels of physical activity. This inconsistency was also observed in several other studies comparing nutritional groups within school-age populations (5,20,22,30,34). Peer pressure and survival needs are cited as the main reasons for this finding (22).…”
Section: Tablementioning
confidence: 56%
“…This observation cannot be compared with other results because previous studies that compared malnourished groups did not include overweight subjects (19)(20)(21)(22)(23). In general, studies that compared marginally malnourished children and adolescents with their normal peers found that absolute levels of maximal oxygen uptake, muscle strength, and anaerobic power are higher in the normal groups, but if the difference in body mass is taken into account, motor performance tends to be equal or even better in the malnourished groups (12,(24)(25)(26)(27).…”
Section: Tablementioning
confidence: 82%
“…Outstanding Indian contributions bearing on the question of "adaptation" to chronic energy deficit, and on the functional significance of small body size, are those of Shetty (59) and Satyanarayana et al (55)(56)(57)(58). These authors emphasize the point that while small body size and behavioral alterations in work patterns arising from chronic energy deficit may facilitate survival under marginal living conditions, they cannot be viewed as beneficial satisfactory adaptive responses consistent with optimal levels of productivity GOPALAN and quality of life.…”
Section: Misuse Of the Term Adaptationmentioning
confidence: 99%
“…All three are of importance for the well-being of children and for the prevention of diseases. It is believed that reductions in body size and wasting of muscle mass are the main contributors to low physical fitness in undernourished children (Malina and Buschang, 1985;Martorell et al, 1992;Satyanarayana et al, 1979;Spurr et al, 1983;Viteri and Turun, 1981). It is suggested that childhood is a sensitive period for the development of malnutrition (World Health Organisation, 1995).…”
mentioning
confidence: 99%